Mesenteric Lymph Drainage Alleviates Acute Kidney Injury Induced by Hemorrhagic Shock without Resuscitation. (25th February 2014) - Zhao, Zi-Gang; Zhu, Hong-Xia; Zhang, Li-Min; Zhang, Yu-Ping; Niu, Chun-Yu
Abstract : This study aimed to investigate the effect of mesenteric lymph drainage on the acute kidney injury induced by hemorrhagic shock without resuscitation. Eighteen male Wistar rats were randomly divided into sham, shock, and drainage groups. The hemorrhagic shock model (40 mmHg, 3 h) was established in shock and drainage groups; mesenteric lymph drainage was performed from 1 h to 3 h of hypotension in the drainage group. The results showed that renal tissue damage occurred; the levels of urea, creatinine, and trypsin in the plasma as well as intercellular adhesion molecule-1 (ICAM-1), receptor of advanced glycation end-products (RAGE), tumor necrosis factor- α (TNF- α ), malondialdehyde (MDA), lactic acid (LA), and 2, 3-DPG in the renal tissue were increased in the shock group after 3 h of hypotension. Mesenteric lymph drainage lessened the following: renal tissue damage; urea and trypsin concentrations in the plasma; ICAM-1, RAGE, TNF- α, MDA, and LA levels in the renal tissue. By contrast, mesenteric lymph drainage increased the 2, 3-DPG level in the renal tissue. These findings indicated that mesenteric lymph drainage could relieve kidney injury caused by sustained hypotension, and its mechanisms involve the decrease in trypsin activity, suppression of inflammation, alleviation of free radical injury, and improvement of energy metabolism.